Zanubrutinib Treatment of Central Nervous System Posttransplant Lymphoproliferative Disorder After Allogeneic Hematopoietic Stem Cell Transplantation: A Case Report - Yang, Ting-Ting; Chen, Wei-Hao; Zhao, Yan-Min; Fu, Hua-Rui; Huang, He; Shi, Ji-Min (Frontiers in Oncology, 2021)
Posttransplant lymphoproliferative disorder (PTLD) is a rare complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT) with poor prognosis. we report a patient with PTLD involved central nervous system (CNS) who treated with zanubrutinib, a second-generation Bruton tyrosine kinase (BTK) inhibitor. Our report supports the efficacy of bruton tyrosine kinase inhibitor zanubrutinib in the treatment of CNS-PTLD, which provides a new therapeutic option.